High school students' interest and attitude toward the vocational courses in the general curriculum in the Division of Bulacan - Reyes, Leonor T. 1910- ([Quezon City University of the Philippines], 1954)
The interest and attitude of third and fourth year high school boys toward vocational courses in Bulacan were examined. Analysis of the data showed that they were vocationally minded. Parents' decision in choice of vocational courses was only subordinate to the students' personal preferences. The most preferred were poultry and swine raising, agronomy and horticulture. The least preferred was automotive. The vocational training given in the secondary schools of Bulacan was relatively adequate.
Bibliography: p. 92-97.
Thesis (M.Ed.)--University of the Philippines, 1954
Typewritten
Vita
Keywords: Vocational education